CRISPR/CasRx Proof-of-Concept for RNA Degradation: A Future Tool against RNA Viruses? - Diana Perez-SanJose; Miguel Angel de la Fuente; Julia Serna Pérez; Maria Simarro; José María Eiros Bouza; Ivan Sanz-Muñoz (MDPI AG, 2021)
Influenza viruses provide a great threat for the human population, causing highly contagious respiratory infections that can lead to serious clinical complications. There are a limited variety of influenza antivirals, and these antivirals are subjected to the constant emergence of resistances. Therefore, the development of new antiviral strategies to combat influenza viruses and other RNA viruses must be promoted. In this work, we design a proof-of-concept of a recently described CRISPR/Cas tool that has been proposed as a possible future RNA virus antiviral, named CRISPR/CasRx. For this, we verified the efficiency of the CasRx endonuclease in the degradation of the eGFP mRNA reporter gene and we established the best conditions for, and the efficient performance of, the CRISPR/CasRx system. The results were measured by fluorescence microscopy, flow cytometry, and qRT-PCR. The analyses demonstrated a reduction in fluorescence, regardless of the amount of eGFP reporter plasmid transfected. The analyses showed an 86-90% reduction in fluorescence by flow cytometry and a 51-80% reduction in mRNA expression by qRT-PCR. Our results demonstrate that the CasRx endonuclease is an efficient tool for eGFP mRNA knockdown. Therefore, subsequent experiments could be useful for the development of a new antiviral tool.